Neotropical migratory birds in Bogota’s parks and gardens: 1945 - 2005 (2012)
The article studies neotropical migratory species watched on Bogota’s parks and gardens, providing the routes preferred by birds nesting in North America that use the city as temporary or transient place during their voyage. By means of two different reports (Borrero, 1945; Echeverry, 2005) it is made clear that the number of individuals has increased in urban areas and, as a result, the ecological, urban and rural conditions that provoked this enhancement are considered. As a conclusion, the article suggests that migratory and resident birds’ conservation require an urban tree planting plan to feed those species at once and, if possible, the construction of artificial lakes to provide them with enough space for lodging.